2011
DOI: 10.1007/s11661-011-0769-x
|View full text |Cite
|
Sign up to set email alerts
|

Role of Chemical Driving Force in Martensitic Transformations of High-Purity Fe-Cr-Ni Alloys

Abstract: The main objective of the present work is to point out the respective roles of chemical driving force and stacking fault energy (SFE) in the occurrence of martensitic transformations in highpurity Fe-Cr-Ni alloys. For this purpose, the transmission electron microscope (TEM), X-ray diffractometer, thermal differential microanalyzer (TDA), and tension test were employed to report M s temperatures, austenite stacking fault energies, and driving forces for the concerned alloys. It was observed that the martensitic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 34 publications
1
20
1
Order By: Relevance
“…7a, the yield strength of the 20/12 and 16/12 alloys is not affected considerably by decrease in the deformation temperature, being consistent with the previous studies [12,13,16,30]. The increase in the yield strength of the 20/10 alloy is related to the formation of spontaneous α 0 -martensite at low temperatures [7]. In contrast, tensile strength and elongation of the alloys are highly dependent on the deformation temperature.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…7a, the yield strength of the 20/12 and 16/12 alloys is not affected considerably by decrease in the deformation temperature, being consistent with the previous studies [12,13,16,30]. The increase in the yield strength of the 20/10 alloy is related to the formation of spontaneous α 0 -martensite at low temperatures [7]. In contrast, tensile strength and elongation of the alloys are highly dependent on the deformation temperature.…”
Section: Resultssupporting
confidence: 89%
“…It has been shown that the deformation-induced martensitic transformations in the Fe-Cr-Ni austenitic alloys occur most probably through the γ-ε-α 0 steps [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6b, the volume fraction of e-and a 0 -martensite phases are both increased with increasing tensile strain, however, the formation of e-martensite is predominant in this steel. This is in contrary to many previous studies in Cr-Ni austenitic steels in which the content of a 0 -martensite phase is increased in the expense of the e-martensite during deformation [49]. Therefore, the deformation path of c ?…”
Section: Phase Evolution In the 025 N Steelcontrasting
confidence: 77%
“…The preferred deformation mechanisms in austenitic stainless steels strongly depend on the stacking fault energy (SFE) [1][2][3]. When the SFE is sufficiently low, the transformation induced plasticity (TRIP) effect occurs upon deformation [4].…”
Section: Introductionmentioning
confidence: 99%